2021
DOI: 10.1055/s-0041-1731910
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of COVID-19 Infection in Cancer Patients in Pune

Abstract: Introduction We document our data on the course of the coronavirus disease 2019 (COVID-19) infection in cancer patients in an attempt to help optimize their management in India and globally. Material and Methods Between February 2020 and January 2021, participating oncologists from Pune (members of the Oncology Group of Pune) documented effect of COVID-19 infection in their cancer patients. Binomial logistic regression analysis as well as correlation analysis was done using Pearson Chi-square test to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…Studies have indicated that malignancy in comparison to other comorbidities is associated with a higher risk of admission to the ICU, invasive ventilation, and death from COVID-19 [ 10 ].It has been reported that mortality rates secondary to COVID-19 in cancer patients are approximately 30% (reported as around 40% in the first wave of COVID-19 and around 25% in subsequent waves),whichis at least 5times higher than inpatients without malignancy [ 1 , 7 , 11 ]. When studies evaluating COVID-19 in patients with solid organ cancers were examined,in a multicenter study from India,the COVID-19-related CFR was determined as 14.4% in solid cancer patients(likelihood ratio of 4.4,p= 0.030), while in a study from Belgium,the 30-day in-hospital COVID-19-related mortality rate was reported as 31.7% in patients with solid cancer and 20.0% in patients without cancer [ 12 , 13 ]. In patients with hematological cancer, a study from Türkiye stated that the rates of severe/critical illness and CFR were significantly higher in hematological cancer patients in comparison withnoncancerous patients (18.9% vs. 11.5% and 13.8% vs. 6.5%, respectively) [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have indicated that malignancy in comparison to other comorbidities is associated with a higher risk of admission to the ICU, invasive ventilation, and death from COVID-19 [ 10 ].It has been reported that mortality rates secondary to COVID-19 in cancer patients are approximately 30% (reported as around 40% in the first wave of COVID-19 and around 25% in subsequent waves),whichis at least 5times higher than inpatients without malignancy [ 1 , 7 , 11 ]. When studies evaluating COVID-19 in patients with solid organ cancers were examined,in a multicenter study from India,the COVID-19-related CFR was determined as 14.4% in solid cancer patients(likelihood ratio of 4.4,p= 0.030), while in a study from Belgium,the 30-day in-hospital COVID-19-related mortality rate was reported as 31.7% in patients with solid cancer and 20.0% in patients without cancer [ 12 , 13 ]. In patients with hematological cancer, a study from Türkiye stated that the rates of severe/critical illness and CFR were significantly higher in hematological cancer patients in comparison withnoncancerous patients (18.9% vs. 11.5% and 13.8% vs. 6.5%, respectively) [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also shown that severe diseasewith the needed forhospitalization/ICU admission and COVID-19-related mortality rates were higher in hematological cancer patients in comparison to solid organ cancer patients [ 12 , 16 , 17 ]. The overall COVID-19-related CFR in the cancer patients in the current study was 15.4% and the rates of hospitalization, ICU admission, and CFR were higher in the hematological cancer patientscompared to thesolid organ cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations